A comparative analysis of nutrition-related assessment criteria and associated nutrition performance scores of food companies across three prominent corporate sustainability assessment tools - Ella Robinson; Jasmine Chan; Meghan O'Hearn; Dariush Mozaffarian; Gary Sacks (Cambridge University Press, 2023)
Abstract Objective: Corporate sustainability assessment tools are increasingly used to evaluate company performance on environmental, social and governance (ESG) criteria. Given the growing burden of diet-related disease and nutrition-related business risks, it is important to understand the scope of nutrition-related ESG data currently available. This study aimed to compare the nutrition-related assessment criteria and associated food company performance across three prominent assessment tools. Design: Key attributes and assessment criteria of two civil society-led and one commercially available corporate sustainability assessment tools were extracted and compared for the year 2021. Company performance scores for twenty-five major food and beverage manufacturers using these three tools were analysed by nutrition domain: 'Product Portfolio', 'Labelling', 'Marketing', 'Accessibility and Affordability', 'Governance and Reporting', 'Stakeholder Engagement' and 'Employee Health'. To enable comparison between tools, company performance scores were assigned to categories of low (score = 0-25 % score or D), moderately low (25-50 % or C), moderately high (50-75 % or B) and high (75-100 % or A). Setting: Global. Participants: N/A. Results: The tools covered similar nutrition domains; however, there was heterogeneity in the assessment criteria used to evaluate each domain. When applied to assess the performance of twenty-five major food and beverage manufacturers, a median nutrition-related performance score of moderately low or low was observed across all tools. The highest scoring domain was 'Governance and Reporting', and the lowest scoring domains were 'Product Portfolio' and 'Accessibility and Affordability'. Conclusions: Greater standardisation of the nutrition-related criteria against which food companies are assessed is needed as part of efforts to drive improvements in food company practices.